Occupational accidents in dental school: a 10-year retrospective - doi:10.5020/18061230.2009.p240 - Ítalo Sarto Carvalho Rodrigues; Isabela Raquel de Araújo Ribeiro; Viviane Maia Araújo; Danilo Lopes Ferreira Lima (Universidade de Fortaleza, 2012)
Objective: To investigate occupational accidents that occurred during the first 10 years of Fortaleza University (UNIFOR) Dental School. Methods: A documental study based on secondary data from the Notification Center of Occupational Accidents of UNIFOR Dental School, reported in the last 10 years. The variables included characteristics of the accidents and of the injured, besides the type of instrument and the resulting injury. Results: Were recorded 160 occupational accidents divided by location, function of the injured and type of accident. It was observed that 63.1% of cases occurred in the Multidisciplinary Clinic, 23.1% in the Integrated Clinic, 8.8% in the laboratories, 1.9% at home, 1.25% in the Surgical Center, 1.25% in the Material Sterilization Central and 0.6% during the training outside university. Concerning the injured, 90.6% of the victims were undergraduates, 5.0% staff, 3.8% teachers and 0.6% patients. Regarding the injury, 40.6% were penetrating bloody injuries, 11.9% cutting bloody injuries, 2.5% cutting non-bloody injuries, 5% burns, 5% penetrating bloody injuries/cutting bloody injuries, 2.5% were injuries with maceration, 1.9% injuries causing ocular trauma and 0.6% of an incident of dog bite. Conclusion: It was concluded that penetrating injuries were prevalent and these occurred mostly in the multidisciplinary clinic, where students of earlier periods of dental course work, indicating that the experience in dental practice generates more care with safety.